Gallium-68 fibroblast activation protein inhibitor positron emission tomography in cardiovascular disease - Mpanya, Dineo; Sathekge, Mike; Klug, Eric; Damelin, Jenna; More, Stuart; Hadebe, Bawinile; Vorster, Mariza; Tsabedze, Nqoba (Frontiers in Nuclear Medicine, 2023)
Gallium-68 fibroblast activation protein inhibitor [(68Ga)Ga-FAPI] is a new radiopharmaceutical positioning itself as the preferred agent in patients with malignant tumours, competing with 2-Deoxy-2-[18F]fluoro-d-glucose [2-(18F)FDG] using positron emission tomography (PET). While imaging oncology patients with [68Ga]Ga-FAPI PET, incidental uptake of [68Ga]Ga-FAPI has been detected in the myocardium. This review summarises original research studies associating the visualisation of FAPI-based tracers in the myocardium with underlying active cardiovascular disease.